PENGAWASAN DAN PERTANGGUNGJAWABAN PERDATA TERHADAP PERTAMBANGAN TIMAH ILEGAL DI KEPULAUAN BANGKA BELITUNG - Anwar, Muhammad Syaiful; Sari, Rafiqa; Satrio, Ndaru (Lembaga Marwah Rakyat, 2024)
The purpose of this research is to develop supervision and accountability towards the environment in a legal state dimension and to determine the ideal form of accountability for illegal miners in the Province of Bangka Belitung Islands. Illegal mining activities damage environmental quality standards both on land and in coastal areas. Based on this, it will become a derivative problem of the mining activity related to civil supervision and accountability for mining activities on land and in coastal areas. This research is a normative juridical study, with data collection methods through library research. The form of environmental supervision of illegal mining can be applied in a sustainable legal state dimension through the integration process of systems, increasing human resource capacity and proving environmental problems preventively and protectively. The ideal form of civil liability can be carried out through litigation and non-litigation, but strengthening is needed through litigation decisions by conducting rehabilitation, reclamation, restoration, and recovery. Keywords: Supervision, Liability, Illegal Mining